PENGEMBANGAN KECERDASAN SPIRITUAL ANAK USIA DINI MELALUI HOMESCHOOLING - Nina Mariana; Abdul Azis; Iwan Setiawan (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Tarbiyah, Institut Agama Islam Darussalam (IAID) Ciamis Jawa Barat, 2019)
The purpose of this study was to determine homeschool planning in developing spiritual intelligence in children aged 0-7 years; to find out the implementation of homeschooling in developing spiritual intelligence in children aged 0-7 years; and to know the advantages and disadvantages of homeschooling in developing spiritual intelligence in children aged 0-7 years. The results showed that: (1) Homeschooling planning in developing spiritual intelligence in children aged 0-7 years at Negla House, the initial stages used by parents in Negla Rumah family is to understand the psychology of children, learn the learning methodology, parents must be the same - same time learning, understanding that compulsory education is actually at the level of primary education not at an early age; (2) Implementation of homeschooling in developing spiritual intelligence in children aged 0-7 years at Negla House, with programs including getting up early, teaching prayers that are applicable, stimulating gross motor and fine motor skills; (3) The advantages of homeschooling in Negla Houses are from the side of the heart, the attachment of parents with children is very close, in terms of cheaper funding, family values ​​are more strongly embedded in children, more can be maximized in preparing children for the next phase, namely the social phase, more honing the spiritual parent. Regarding the lack of homeschooling, when parents are not optimal in teaching patience to children in the learning process, children's spiritual intelligence will not appear optimally and the lack of community response to homeschooling.